2008
DOI: 10.1371/journal.pgen.1000024
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of the MHC in Autoimmunity: A Review and Pooled Analysis

Abstract: The major histocompatibility complex (MHC) is one of the most extensively studied regions in the human genome because of the association of variants at this locus with autoimmune, infectious, and inflammatory diseases. However, identification of causal variants within the MHC for the majority of these diseases has remained difficult due to the great variability and extensive linkage disequilibrium (LD) that exists among alleles throughout this locus, coupled with inadequate study design whereby only a limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
385
1
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 514 publications
(413 citation statements)
references
References 94 publications
12
385
1
15
Order By: Relevance
“…Numerous genes are thought to be associated with an increased risk of developing certain autoimmune diseases. The human leukocyte antigen (HLA) genes are among the strongest predictors of risk for autoimmune conditions (see review by Fernando et al 28 ). Different HLA haplotypes are also associated with neurodevelopmental disorders, such as schizophrenia and ASD (Table 3).…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%
“…Numerous genes are thought to be associated with an increased risk of developing certain autoimmune diseases. The human leukocyte antigen (HLA) genes are among the strongest predictors of risk for autoimmune conditions (see review by Fernando et al 28 ). Different HLA haplotypes are also associated with neurodevelopmental disorders, such as schizophrenia and ASD (Table 3).…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%
“…The most consistently reproducible finding is HLA-DRB1*0701 [170][171][172][173] Ulcerative colitis HLA-DRB1*0103 and *1502 HLA-DRB1*0103 is the most reproducible association 170,174,175 Graves disease HLA-DRB1*03-DQB1*02-DQA1*0501 Logistic-regression analysis shows that the association could be explained by either DRB1 or DQA1 176,177 Hashimoto 0 s thyroiditis HLA-DRB1*04-DQB1*03-DQA1*03…”
Section: Regulation Of Mhc Class II Gene Expressionmentioning
confidence: 99%
“…Our findings are similar with those of several recent reports, which showed that the flCTLA4 protein and sCTLA4 mRNA levels were decreased in myasthenia gravis patients, 29,41 and sCTLA4 protein levels were decreased in individuals with diabetes, Behcet's disease and abdominal aortic aneurysm; [42][43][44] however, Wong et al 45 have shown increased levels of the sCTLA4 protein in systemic lupus erythematosus. Possible mechanisms producing different levels of sCTLA4 levels in autoimmune diseases could be: (1) stimulation of T lymphocytes results in significantly decreased expression of sCTLA4, 15 (2) there are cell types other than T cells expressing CTLA4, for example, skeletal muscle cells and granulocytes, 46,47 which also may express sCTLA4 and secrete into serum, (3) protein levels are affected not only by mRNA levels; and (4) differential sCTLA4 levels may correlate with different CTLA4 genotypes, disease types and immunological states. All of these mechanisms support a relationship between expression of CTLA4 and autoimmune diseases.…”
Section: Ctla4 Gene Polymorphisms In Ucmentioning
confidence: 99%
“…Polymorphisms of human leukocyte antigen, particularly human leukocyte antigen class II alleles DRB1*1502 in populations of Asian and European ancestry and DRB1*0103 in populations of European ancestry, were the first consistent UC risk polymorphisms identified. 2 Recent genome-wide association studies (GWAS) in both UC and CD have established multiple genes and loci as UC risk factors. TNFSF15 (tumor necrosis factor receptor superfamily 15), identified in the first CD GWAS in the Japanese population, was shown to be associated with an increased risk for UC and CD in a British study.…”
Section: Introductionmentioning
confidence: 99%